TH6.5 Perioperative group and save testing are not routinely indicated for emergency laparoscopic appendicectomy and laparoscopic hernia repairs. (9th August 2022) - Reece, Ieuan; Shakweh, Ealaff; Britton, Clemency; Chen, Jun Yu; Zafar, Norman; Al-Musawi, Jasim
Abstract: Introduction: Major haemorrhage is a rare complication of laparoscopic hernia repair and laparoscopic appendicectomy. It is common practice for patients undergoing these procedures to have 2 valid group and saves preoperatively, however perioperative blood transfusions for these patients is seldom required. Obtaining valid samples is not only financially burdensome but frequently leads to delays in theatre lists and patient care. Our unit therefore performed a retrospective cohort analysis to investigate blood transfusions performed perioperatively and within 28 days of laparoscopic appendicectomy and laparoscopic hernia repairs. Method: We used our electronic records system to collect data of all laparoscopic appendectomies and laparoscopic hernia repairs between March 2017-March 2021. Patients of any age undergoing laparoscopic appendicectomy or laparoscopic hernia repair were included. Patients requiring concomitant intra-abdominal surgery or had incomplete medical records were excluded. Results: 1893 patients were included in the study of which 1464(77.3%) had a laparoscopic appendicectomy vs 429(22.7%) laparoscopic hernia repair. In total 3511 group and saves were taken costing £47, 398.50. Only 1 patient (0.068%) required an emergency blood transfusion (4 units of red cells) secondary to major haemorrhage and 2 patients (0.11%) required pre-operative transfusions for anaemia. Conclusion: Our findings demonstrate that the incidence of perioperative blood transfusions for laparoscopic appendicectomy and laparoscopic hernia repairs is low, challenging the indication for routine preoperative group and saves. Considering our findings, the burden of cost, patient discomfort and theatre delays; we advocate a more nuanced approach to preoperative group and saves, reserving these for patients stratified as high risk.